Answers

2015-11-27T21:54:47+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
When simplified we get LHS=RHS
1-3/1+3=2*1/4-1
-1/2=-1/2
2 3 2
2015-11-29T06:16:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We know that, tan60°=√3.Therefore tan^2 60°=3 And cos60°=1/2.Therefore cos^2 60°=1/4. Given: to prove that 1-tan^2 60°/ 1+tan^2 60°= 2 cos^2 60° - 1. 1-3/1+3=(2×1/4)-1 We get as -1/2=-1/2 Therefore L.H.S=R.H.S HENCE PROVED
2 5 2